HOW AN ENGLISH BOOK ILLUSTRATES GENDER ROLE IN THIS ERA: A CRITICAL REVIEW - Tri Wahyuni Floriasti (ETERNAL (English Teaching Journal), 2016)
Language is a tool to express feeling, idea, and share information. Language reflections  the speakers who have many things in common such as tradition, background, values and customs, then they have their own culture in communication among them.  Thus, it can be said that they have their own standard for leveling the social class, sexual orientation, language home, and gender roles in the society. Since language is a part of culture so  learners need to be aware of values in the society. For instance, learners, speakers of the language itself  or whoever interest  to  the language need to see the roles of male and female in the professional   and daily life which has been shifted from unpopular profession for female workers to favored career.  It cannot be ignored that in the  dreality, several English guidebooks for students still contain unresponsive gender pictures as media to introduce English material.  Women are profiled as nurses, housekeepers, nannies, and other unpopular positions while man  are figured as directors, CEO, pilots, doctors, and other most-wanted careers. In fact, the roles of women and men have been shifted and they have  equal   position now in professional life. This situation turned teachers and lecturers to be more creative in designing innovative material. Thus, teachers need to integrate not only such important points as good English material but also knowledge of gender into students’ materials. Therefore, learners and the society get and apply the knowledge and start appreciating each other, both men and women.